Improving teachers’ skills on developing competence-based of e-student whorksheet - Daroe Iswatiningsih; Fida Pangesti; Lila Puspitasari; D. Dluhayati (Universitas Muhammadiyah Malang, 2022)
The Covid-19 pandemic has changed the learning process from offline to online. In responding to this change, innovations and the use of technology are needed so that learning process runs well and the goals set are achieved properly. One of an important material inlearning is student worksheet. This community service program aimed at providing assistance in preparing competency-based of electoric student worksheet (e-student worksheet) using Google Form platform. The targeted participants of this activity were principals and all teachers of SMPN 25 Malang. The methods applied were workshop and mentoring. The workshop was delivered informatively with the materials that focused on student worksheet, e- student worksheet, and the use of Google Forms in preparing e-student worksheet. The results of this activity were the skills gained by participants in terms of compiling e-student worksheet. The participants have prepared student worksheet for blended learning. This e-student worksheet resulted was then implemented in the even semester of the 2020/2021 school year.